2005
DOI: 10.1002/app.21782
|View full text |Cite
|
Sign up to set email alerts
|

An improved prediction result of entropic‐FV model for vapor–liquid equilibria of solvent–polymer systems

Abstract: ABSTRACT:In this work, entropic expressions of UNI-FAC-FV and Entropic-FV models were evaluated by using an extensive database of infinite dilution vapor-liquid equilibrium (VLE) data of athermal systems containing polypropylene, polyethylene, and polyisobutylene. For the infinite dilution athermal systems, performance of the Entropic-FV model was better than that of the UNIFAC-FV model. Then, finite concentration VLE data of non-athermal systems that consisted of 16 polymers and 36 solvents containing a large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…They reported that the entropic expression (combinatorial and free-volume) of the Entropic-FV model performed better than that of UNIFAC-FV model for the athermal systems studied. The same result was also demonstrated in our previous work [6].…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…They reported that the entropic expression (combinatorial and free-volume) of the Entropic-FV model performed better than that of UNIFAC-FV model for the athermal systems studied. The same result was also demonstrated in our previous work [6].…”
Section: Introductionsupporting
confidence: 89%
“…The residual contribution accounts for the effect of enthalpy of mixing, where both models use the residual contribution of the UNIFAC model with group interaction parameters obtained from VLE data of low-molecular-weight substances. In our previous works [5,6], we proposed revised group interaction parameters for the UNIFAC-FV and Entropic-FV models determined from VLE data of solvent-polymer systems. However, the revised parameters did not provide an improvement for systems containing nonpolar solvents, and the application was limited to only a small number of systems due to the limited group parameters proposed.…”
Section: Introductionmentioning
confidence: 99%
“…where X m was the mole fraction of group m in the solution and X i m the mole fraction of group m in certain molecule i. X m and X i m was calculated by eqn (20) and (21)…”
Section: Modification Of the Unifac-zm Modelmentioning
confidence: 99%
“…17 Unfortunately, the group contribution methods discussed above also show the weak prediction for polymer system. Though models of UNIFAC-FV 18,19 and Entropic-FV 20 have been developed for polymer system and the precision is improved, the universality of free volume contribution is not enough and the usage is not convenient for the accurate volume parameter of polymer and small molecule. UNIFAC-ZM model proposed by Zhong et al 21 added a universal parameter for the modication of the combined term, which was different from other models.…”
Section: Introductionmentioning
confidence: 99%
“…One important difference between ordinary mixtures and mixtures containing polymers is the nonnegligible change of free volume (FV) , upon mixing. For example, Oishi et al developed a free volume term for the UNIFAC model and Entropic-FV models adopted the free volume term developed by Elbro et al Recently, many improvements have been proposed based on the above two activity coefficient models by modifying the free volume term and group interaction parameters. Comparison of the performance of different methods in vapor–liquid equilibria (VLE) of polymer solutions can be found in the work of Costa et al Kontogeorgis et al and Bogdanic et al summarized the performances of several predictive group contribution models for the liquid–liquid equilibrium (LLE) prediction in polymer solutions.…”
Section: Introductionmentioning
confidence: 99%